2021
DOI: 10.3389/fmicb.2021.637811
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends of Benthic Bacterial Diversity and Community Composition Along Organic Enrichment Gradients of Salmon Farms

Abstract: The analysis of benthic bacterial community structure has emerged as a powerful alternative to traditional microscopy-based taxonomic approaches to monitor aquaculture disturbance in coastal environments. However, local bacterial diversity and community composition vary with season, biogeographic region, hydrology, sediment texture, and aquafarm-specific parameters. Therefore, without an understanding of the inherent variation contained within community complexes, bacterial diversity surveys conducted at indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 175 publications
(247 reference statements)
3
25
0
Order By: Relevance
“…These bacteria have been reported as microbes related to aquaculture operations. For instance, sulphate-reducing bacteria such as members of the family Desulfovibrionaceae have been found to be enriched in sediments by aquaculture activity (Blancheton et al, 2013; Aranda et al, 2015; Frühe et al, 2021). Sulphate reducing bacteria can be enriched by high levels of organic matter relying on, for instance, fermented to acidic end products (i.e., by Psychromonadaceae, Vibrionaceae , and other marine (facultatively) anaerobic chemoorganotrophs), leading to the increased production of H 2 S (Barton and Hamilton, 2007; Kwon et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These bacteria have been reported as microbes related to aquaculture operations. For instance, sulphate-reducing bacteria such as members of the family Desulfovibrionaceae have been found to be enriched in sediments by aquaculture activity (Blancheton et al, 2013; Aranda et al, 2015; Frühe et al, 2021). Sulphate reducing bacteria can be enriched by high levels of organic matter relying on, for instance, fermented to acidic end products (i.e., by Psychromonadaceae, Vibrionaceae , and other marine (facultatively) anaerobic chemoorganotrophs), leading to the increased production of H 2 S (Barton and Hamilton, 2007; Kwon et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These include members of the taxa Psychromonadaceae ( Psychromonas ), Fusobacteriales (Fusobacteriaceae), Vibrionaceae, Desulfovibrionaceae (Desulfovibrio), Sulfurimonadaceae (Sulfurimonas), Sulfurovaceae (Sulfurovum), Fusibacteraceae (Fusibacter), Rhizobiales , and Sphingomonadaceae . Various microbial groups have been associated with marine environments receiving high level of nutrients and some have been reported as potential aquaculture impact biomarkers in the past (Blancheton et al, 2013; Kandel et al, 2014; Rasigraf et al, 2017; Verhoeven et al, 2018; Yang et al, 2019; Haro-Moreno et al, 2020; Zhang et al, 2020; Aalto et al, 2021; Dully et al, 2021; Frühe et al, 2021; Mahmoud and Magdy, 2021; Pan et al, 2021). According to these studies, such taxa are usually found in high abundance in near-cages sites, including Sulfurovum, Vibrionaceae, Desulfovibrionaceae, Methylotenera, Hyphomonadaceae, Spirosomaceae and Fusibacter, Flavobacteriaceae (NS3a marine group) and Bacteriovoracaceae .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations